History and Stages of Development of Uzbek Folk Arts - Abdumalikovna, Khakimova Gulnora; Arifovna, Kadirova Nozima (European Journal of Life Safety and Stability (2660-9630), 2022)
Patterns and paintings, the alphabet of applied decorative art, are one of the oldest forms of folk applied art. Man-made pearls are not only used in all kinds of applied arts, but also in architectural decorations of buildings and structures.